2003
DOI: 10.1097/01.lab.0000097189.79233.d8
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin/Tek Interactions Regulate MMP-9 Expression and Retinal Neovascularization

Abstract: SUMMARY:The objective of the study was to determine the role of the angiopoietins in the regulation of gelatinase expression during angiogenesis, and whether inhibition of the angiopoietin/Tek interaction in vivo can suppress the extent of retinal neovascularization. Retinal microvascular endothelial cells were treated with angiopoietins and examined for the production of gelatinases. The effects of inhibiting angiopoietin binding to the Tie-2 receptor was studied in newborn mice with experimentally induced re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 34 publications
3
52
0
Order By: Relevance
“…However, to date, no defined mechanistic experiments have been performed that unambiguously demonstrate cellular effector functions for Ang-2 that are compatible with an antagonistic mode of action towards Tie-2. Instead, increasing evidence supports the notion that long-term stimulation of cultured endothelial cells with Ang-2 exerts agonistic Tie-2-activating functions, as evidenced by Tie-2 receptor phosphorylation (Teichert-Kuliszewska et al, 2001), sprouting angiogenesis (Korff et al, 2001;Mochizuki et al, 2002;Teichert-Kuliszewska et al, 2001), increased MMP-9 expression (Das et al, 2003) and endothelial-cell survival (Kim et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, no defined mechanistic experiments have been performed that unambiguously demonstrate cellular effector functions for Ang-2 that are compatible with an antagonistic mode of action towards Tie-2. Instead, increasing evidence supports the notion that long-term stimulation of cultured endothelial cells with Ang-2 exerts agonistic Tie-2-activating functions, as evidenced by Tie-2 receptor phosphorylation (Teichert-Kuliszewska et al, 2001), sprouting angiogenesis (Korff et al, 2001;Mochizuki et al, 2002;Teichert-Kuliszewska et al, 2001), increased MMP-9 expression (Das et al, 2003) and endothelial-cell survival (Kim et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, VEGF increases both expression and release of MMP-2 and MMP-9 (Lamoreaux et al, 1998;Rooprai et al, 2000;Wang and Keiser, 1998). More recently, Ang-1 have been also described to interfere with MMP-2 and MMP-9 expressions (Das et al, 2003;Kim et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A consistent body of experimental evidence has shown that in the initial steps of angiogenesis, the matrix metalloproteinases (MMPs) play an important role in the degradation of the basal lamina and the invasion of endothelial cells (Pepper, 2001). In addition, angiogenic factors such as VEGF and Angs could regulate MMP expressions and/or activities (Das et al, 2003;Wang and Keiser, 1998). However, proteolytic enzymes such as MMPs, in particular MMP-2 and MMP-9, could contribute to BBB injury in cerebral ischemia .…”
Section: Introductionmentioning
confidence: 99%
“…MMP-1, MMP-2, and MMP-9 are produced during EC migration and endothelial tubule formation. 22,23 We concentrated on MMP-9 activity because we previously demonstrated that VEGF stimulated MMP-9 activity in EC and smooth muscle cell cultures. 24 We found that MMP-9 activity was greatly increased in the group treated with VEGF plus Ang-2, compared with the group treated with VEGF alone, suggesting that Ang-2 may induce MMP-9 activation.…”
Section: Discussionmentioning
confidence: 99%